2012
DOI: 10.2308/iace-50119
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and Accounting Education

Abstract: The current study investigates how a university accounting education affects the rationales used by accounting and first-year business students in making ethical decisions, the level of deliberative reasoning they employ, and their ethical decisions. Senior accounting students (with approximately four accounting courses to complete) were found to exhibit higher deliberative reasoning, make more frequent use of post-conventional modes of deliberative reasoning, and make more ethical decisions than first-year ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
0
13
0
5
Order By: Relevance
“…As trong research body exists for the moral judgement component (Thomas, 2012;Dellaportas, 2006;Shaub, 1994;Armstrong, 1993;Welton et al,1 994); however, there seemst ob eagap in the other three processes. The construct of ethical sensitivity, specifically, seemst oh avebeenneglected.…”
Section: Introductionmentioning
confidence: 99%
“…As trong research body exists for the moral judgement component (Thomas, 2012;Dellaportas, 2006;Shaub, 1994;Armstrong, 1993;Welton et al,1 994); however, there seemst ob eagap in the other three processes. The construct of ethical sensitivity, specifically, seemst oh avebeenneglected.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with what scholars have identified as deliberative ethical reasoning -defined as the "actual level of ethical reasoning that an individual is using in a particular context" (Thomas, 2012, 400) -which is distinct from cognitive moral capability, or "the level of ethical reasoning that an individual is capable of in general contexts" (Thomas, 2012, p. 400). Because deliberative reasoning is normally applied within specific contexts and domains of knowledge, it is thought to be more proximally associated with ethical action than cognitive moral capability (Thorne, Massey, & Magnan, 2003), and it can be developed in undergraduate business students (Thomas, 2012).…”
Section: Article In Pressmentioning
confidence: 99%
“…Although there is still some debate regarding the efficacy of ethics training (e.g., Lund Dean & Beggs, 2006;Taft & White, 2007), recent evidence is encouraging. For example, studies by Lau (2010), Klimek and Wenell (2011), and Thomas (2012) found significant differences in the ethical reasoning abilities of undergraduate business students exposed to ethical training.…”
Section: Introductionmentioning
confidence: 94%
“…Hombres (222) Mujeres (207 Las puntuaciones medias asignadas por los alumnos de último curso son mayores que las puntuaciones medias de los alumnos de primero, estos resultados coincidirían con las conclusiones del trabajo de Thomas (2012). A su vez, las puntuaciones medias de los egresados son superiores a las puntuaciones de los alumnos de último curso, con la excepción de "Solidaridad" e "Internacionalización".…”
Section: Estadísticos Descriptivos Por Sexounclassified